Laparoscopic Surgery Can Reduce Postoperative Edema Compared with Open Surgery - Dong Guo; Jianfeng Gong; Lei Cao; Yao Wei; Zhen Guo; Weiming Zhu (Gastroenterology Research and Practice)
Aim. The study aimed to investigate the impact of laparoscopic surgery and open surgery on postoperative edema in Crohn’s disease. Methods. Patients who required enterectomy were divided into open group (Group O) and laparoscopic group (Group L). Edema was measured using bioelectrical impedance analysis preoperatively (PRE) and on postoperative day 3 (POD3) and postoperative day 5 (POD5). The postoperative edema was divided into slight edema and edema by an edema index, defined as the ratio of total extracellular water to total body water. Results. Patients who underwent laparoscopic surgery had better clinical outcomes and lower levels of inflammatory and stress markers. A total of 31 patients (26.05%) developed slight edema and 53 patients (44.54%) developed edema on POD3. More patients developed postoperative edema in Group O than in Group L on POD3 (p=0.006). The value of the edema index of Group O was higher than that of Group L on POD3 and POD5 (0.402±0.010 versus 0.397±0.008, p=0.001; 0.401±0.009 versus 0.395±0.007, p=0.039, resp.). Conclusions. Compared with open surgery, laparoscopic surgery can reduce postoperative edema, which may contribute to the better outcomes of laparoscopic surgery over open surgery.